Pragmatic Elements in English as a Foreign Language (EFL) Textbooks in Senior High Schools of Pekanbaru - Joko Ariyanto; Raja Syamsidar; Juswandi Juswandi; Hermanysah Hermanysah; Fitra Elia (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This study aims to analyze the pragmatic elements present in English as a Foreign Language (EFL) textbooks used in senior high schools in Pekanbaru, Indonesia. Specifically, it examines the coverage of speech acts, metapragmatic strategies, and contextual variables in two widely used textbooks: Buku Sarana Elektronik (BSE) and Pathway to English, for grades X, XI, and XII. The research employs a qualitative descriptive approach with document analysis techniques, drawing data from the textbooks and interviews with English teachers in Pekanbaru. The findings reveal that the coverage of speech acts in both textbooks is incomplete, with an overemphasis on directives such as commands, requests, and suggestions. These speech acts, often face-threatening, require higher pragmatic competence from learners, which the textbooks do not adequately support. Additionally, metapragmatic information provided in the textbooks is limited and focuses more on pragmalinguistics than sociopragmatic factors, leaving students underprepared for real-life communication where social norms and contextual variables such as power dynamics play a crucial role. The textbooks also lack diversity in contextual variables, with most dialogues featuring interactions between individuals of equal power and little social distance, reducing learners’ exposure to various social roles and communication contexts. The study concludes that both BSE and Pathway to English fail to provide sufficient pragmatic content and suggests that future textbook design should include a broader range of speech acts, metapragmatic strategies, and diverse social contexts to better develop learners' pragmatic competence. The findings have significant implications for improving the effectiveness of teaching materials in Indonesian EFL classrooms.